PHILOSOPHICAL ESSENCE OF FAMILY CEREMONIES OF THE UZBEK PEOPLE (TAMADDUN NURI JURNALI, 2024)
The family rituals of the Uzbek people have been formed over centuries, enriched with modern elements and are developing. Any ceremony is a social reality, develops and improves. Family rituals of the Uzbek people are an axiological reality with their own moral evolutionary development and separate periods of development. In this article, a philosophical analysis is made of the need to introduce specific regulations in the development of national values ​​and to preserve the rituals in their true essence.